The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ma14051173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Protection of Pharmaceutical Kaolin and Talc Modified with Copper and Zinc

Abstract: Six pharmaceutical pastes were prepared using chemically modified kaolin and talc powders. Tests were conducted to determine their structural and chemical characteristics as well as their antimicrobial protection, thus rendering them suitable for cosmetic and pharmaceutical uses. Kaolin and talc were treated chemically via the cation exchange method to load the clay particles with copper and zinc ions, two cations well known for their antimicrobial properties. Mineralogical analyses were conducted by using X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
(55 reference statements)
0
8
0
9
Order By: Relevance
“…There are several PET Protocols, like the compendial methods of European and U.S. Pharmacopoeia, or ISO 11930. During this study, an alternative PET Protocol has been used, known as mixed Protocol, which is based on the compendial protocols but is more demanding [ 56 ]. The mixed protocol is based on the compendia methods and includes eleven (11) Gram-positive and Gram-negative bacteria, yeast, and molds ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several PET Protocols, like the compendial methods of European and U.S. Pharmacopoeia, or ISO 11930. During this study, an alternative PET Protocol has been used, known as mixed Protocol, which is based on the compendial protocols but is more demanding [ 56 ]. The mixed protocol is based on the compendia methods and includes eleven (11) Gram-positive and Gram-negative bacteria, yeast, and molds ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this result is corroborated by other authors like Jou et al, (2016) [ 67 ] and Holesova et al, (2013) [ 68 ] which reported that natural clay minerals show no antibacterial effect. Therefore, the antibacterial properties of clay minerals are attributed to coexisting inorganic species such as Zn [ 56 , 69 , 70 ] and Cu ions [ 56 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 10 1 cfu : μέγιστος αριθμός αποδοχής = 20 Συγκεκριμένα, σχετικά χαμηλές κορυφές που υποδεικνύουν μικρές ποσότητες περίπου 4% (χαμηλές ανακλάσεις), πιθανώς οξειδίων χαλκού και ψευδαργύρου αντίστοιχα. (Martsouka et al, 2021a). Τέλος, οι πειραματικές διαδικασίες με αιθυλενογλυκόλη, επιβεβαίωσαν τα αποτελέσματα των ορυκτολογικών αναλύσεων (Εικόνα 4Β).…”
Section: για το κριτήριο βunclassified